La cerámica andalusí - Álvaro Zamora, María Isabel (Artigrama, 2007)
Síntesis de la cerámica andalusí en la que se trata de sus obradores y de las aportaciones técnicas más relevantes de la vajilla y de la cerámica de aplicación arquitectónica, indicando sus precedentes y relación con otras producciones islámicas, características, evolución e influencia posterior. Se concluye con una selección bibliográfica comentada.Synthesis of al-Andalus’ ceramics, concerning especially to its workshops and the most important technical developments related to the crockery and to its use in Architecture. The article indicates both some of its precedents and its relation to other Islamic productions, as well as its main features, evolution and subsequent influences. Finally, a commented selection of bibliography is provided.